2020
DOI: 10.1101/2020.08.11.246025
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Occurrence, identification and antibiogram signatures of selected Enterobacteriaceae from Tsomo and Tyhume rivers in the Eastern Cape Province, Republic of South Africa

Abstract: The increasing occurrence of multidrug-resistant Enterobacteriaceae in clinical and environmental settings has been seen globally as a complex public health challenge, mostly in the developing nations where they significantly impact on freshwater used for a variety of domestic purposes and irrigation. In this paper, we give details as regards the occurrence and antibiogram signatures of Enterobacteriaceae community in Tsomo and Tyhume rivers within the Eastern Cape Province, Republic of South Africa using stan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
0
4
1
Order By: Relevance
“…Interestingly, the MAR index value of 129 MDR strains ranged from 0.23 to 0.69, with an average of 0.40. Although these findings were lower than that of the other study [ 29 ], the MAR indices observed in this study were > 0.2. A MAR index of 0.2 or higher indicates high-risk sources of contamination [ 30 , 31 ].…”
Section: Discussioncontrasting
confidence: 97%
“…Interestingly, the MAR index value of 129 MDR strains ranged from 0.23 to 0.69, with an average of 0.40. Although these findings were lower than that of the other study [ 29 ], the MAR indices observed in this study were > 0.2. A MAR index of 0.2 or higher indicates high-risk sources of contamination [ 30 , 31 ].…”
Section: Discussioncontrasting
confidence: 97%
“…Some other researchers have also described the dominance of the bla CTX-M variants in many different surface water (Zarfel et al, 2013;Zurfluh et al, 2013;Ojer-Usoz et al, 2014). Also, the bla CTX-M variants are among the most widespread in South Africa (Njage and Buys, 2015;Fadare et al, 2020). Interestingly, we discovered isolates from various genera such as E. cancerogenus, E. cloacae, C. koseri, C. freundii, K. oxytoca, K. pneumoniae, and E. coli harbouring the various bla CTX-M variants.…”
Section: β-Lactamases Detected In Effluents Of Wastewater Treatment Plantsmentioning
confidence: 51%
“…The quality of an effluent discharge is particularly an important criterium in assessing the efficiency of a WWTP. The surface water which receives these municipal WWTP effluents are being abstracted for irrigation, domestic, and religious activities (Fadare et al, 2020), thereby being a public health concern as they are unsuitable for domestic uses.…”
Section: Total Quantification and Identification Of Enterobacteriaceae In The Wastewater Treatment Plantsmentioning
confidence: 99%
“…Twenty-nine of the isolates used in this current study were part of our earlier studies. The description of the study sites, sample collection and processing, and isolation were carried out as reported in our previous studies 33 35 . The isolates in this study include, 33 Klebsiella pneumoniae recovered from freshwater sources (n = 7), hospital wastewater (HWW) (n = 9), and wastewater treatment plant effluents (WWTP) (n = 7), while the remaining were isolated from animal droppings (FD).…”
Section: Methodsmentioning
confidence: 99%
“…For subsequent analysis, single pure colonies were transferred to 2 ml BHI broth and incubated overnight at 37 °C. The boiling method 36 was used to extract the genomic DNA with slight modifications, as previously reported elsewhere 35 . The DNA-containing supernatant was then transferred to sterile microcentrifuge tubes (Eppendorf, Germany) and stored at – 20 °C for future assays.…”
Section: Methodsmentioning
confidence: 99%